HUBUNGAN ANTARA BEBAN KERJA FISIK DENGAN TINGKAT KEBUGARAN JASMANI PEKERJA BAGIAN GROUND HANDLING DI BANDARA AHMAD YANI SEMARANG (Studi Kasus pada Pekerja Porter PT. Gapura Angkasa) - Rahmawati, Fifi; Suroto, Suroto; Wahyuni, Ida (Jurnal Kesehatan Masyarakat (e-Journal), 2016)
Porter is a part of ground handling. This is the hardest job that rely on physical ability workers to lift weights either manually or with mechanical devices support. Physical fitness is very important to maintain the condition of workers in order to enhance to work optimally. The purpose of research was to analyze the relationship between physical work load with the level of physical fitness on ground handling workers of PT. Gapura Angkasa at the Ahmad Yani Airport in Semarang. This reaserch used a quantitative method with cross sectional approach. The sample of this research were 39 porters of PT. Gapura Angkasa obtained using purposive sampling with inclusion criteria of working on the morning shift, normal blood pressure, and willing to become respondents. The research variables were age, nutritional status, tenure, exercise habits, smoking habits, physical workload, and physical fitness. Data collection method in this reaserch used questionnaires, observations, and 3 minutes harvard step test. The results of univariate analysis obtained the highest working age of 18-25 years old (53.8%), normal nutritional status of workers (64.1%), job tenure <1 year (53.8%), less exercise habits (89.7%), smoking habits of workers (53.8%), Â heavy physical workload (71.8%) and less physical fitness (43.6%). The result of statistical test using rank spearrman indicated that there was no relationship between age (r = 0.306, p = 0.058), nutritional status (r = -0.178, p = 0.279), and job tenure (r = 0.010, p = 0.953) with the level of physical fitness. There was a relationship between exercise habits (r = -0.464, p = 0.003), smoking (r = -0.633, p = 0.000016), and physical workload (r = -0.326, r = 0.043) with the level of physical fitness. The workers need to exercise regularly to keep good physical fitness.